Investigation of the effect of blade geometry on blood trauma and pump performance - Ding, Yi (2008)
Five different blade geometries are investigated in this project. The objective is to establish the effect of b variation on the flow pattern and head generated. Their 3-D pump models are simulated using CFX-TASC flow. Generally, the results showed that the new impeller designs gave better pump performance and flow patterns as compared to the radial straight blade.